Broom Tech : Broom Roller / Saiful Amirul Asraf Mohd Halid ...[et al.] - Mohd Halid, Saiful Amirul Asyraf; Ab. Razak, Muhammad Zukfathi; Fauzi, Mohammad Fauzan; Che Ismail, Muhammad Hakimi; Norlee, Muhammad Amer Safwan (2016)
Generally our company name is Broom Tech which we sell advanced broom to community. At this moment, Malaysia seems so down in currency. Then an idea just pop out that we, the five of us wanted to get involved in business in order survive the economy as well as to assist nation economy. As all of us are mechanical student, we have seen eye to eye to sell advanced broom by applying our mechanical skills